Virtual high-throughput screening: potential inhibitors for the mycobacterial α-subunit of tryptophan synthase. Issue 4 (4th March 2022) - Mohan, Surender; Jade, Dhananjay; Gupta, Sonal; Ayyamperumal, Selvaraj; Chandrasekar, M. J. N; Nanjan, M. J.
ABSTRACT: Mycobacterium tuberculosis (Mtb), which causes tuberculosis (TB), is the world's most successful pathogen. If it is to survive in phagosomes, the tryptophan biosynthetic pathway is essential. The α-subunit of tryptophan synthase (TRPS) executes the irreversible catalysis of indole-3-glyceral-3-phosphate to generate indole. The β-subunit catalyses the conversion of indole and serine to tryptophan. Targeting the TRPS α-subunit may, therefore, render the enzyme inactive. The crystal structure of α-subunit downloaded from the protein data bank (PDB: 5OCW) has gaps at the amino acid sequence positions in three places. We, therefore, retrieved the entire amino acid sequence of the protein from the UniProt and built a complete protein structure by adding the missing amino acids using a Modeller. The 3D model of the α-subunit was then used as the target to develop inhibitors for Mtb. We downloaded 58, 699 natural products from the Maybridge database. After space filtering, molecular docking, molecular dynamic simulation and binding free energy calculation were done to develop inhibitors for the TRPS α-subunit. Out of the 18 compounds selected, five virtual hit compounds, namely MFCD00103482, MFCD00118123, MFCD04110719, MFCD01005315 and MFCD04112426, bind well to the TRPS α-subunit. These five potential inhibitors for Mtb will be taken for preclinical testing.